The Use of Social Media as a Platform for Obtaining and Disseminating Da'wah Content by College Students - Ratmiati Ratmiati; Hadi Syabri; Fahmi Faziola; Ibnu Jarir Atha Bari; Fazrul Azmi (Journal of Islamic Education Students (JIES), 2023)
The Information Technology era inseparably intertwines students' behavior with internet usage through computers, laptops, and gadgets. Da'wah (Islamic preaching) is a responsibility for every Muslim, regardless of their profession, requiring effective means for its delivery. Social media serves as a platform for accessing and disseminating moral messages of da'wah. This qualitative descriptive research focuses on the utilization of social media by students for obtaining and spreading Islamic da'wah content. The study involves students of Islamic Education at UIN Batusangkar, specifically the 2023 cohort. Data collection employed a questionnaire distributed to 50 students from December 6 to December 15, 2023. Key findings reveal that 100% of students possess social media applications, with 86% favoring Instagram. Furthermore, 100% have encountered digital da'wah, 78% consistently receive it through the "For You Page" (FYP) feature, and 94% have shared digital da'wah. The predominant platform for disseminating da'wah content is WhatsApp (78%), driven by the goal of earning continuous rewards (pahala jariyah) for sharing beneficial knowledge (88%).